Novel Spectrophotometric Methods For The Determination Of Entecavir In Pharmaceutical Dosage Forms - M. RAJESWARI; P. SUBRAHMANYAM; G. DEVALA RAO; G. SUDHAKAR SAI BABU (International Journal of Pharma and Bio Sciences, 2011)
Three simple and sensitive Spectrophotometric methods (A, B & C) have been developed for the estimation of Entecavir (ETV) in pure and pharmaceutical dosage forms. Method A is based on the formation of colored species by redox reaction with Folin-Ciocalteau (FC) phenol’s reagent under alkaline conditions (λmax: 750 nm). Method B is based on oxidative coupling of the drug with 3-methyl-2-benzothiazolinone hydrazone HCL (MBTH) in the presence of ferric chloride (λmax: 650 nm).Method c is based on formation of Schiff’s base by the condensation of drug with p-dimethyl amino benzaldehyde (PDAB) under acidic conditions (λmax: 430 nm). These methods have been statistically evaluated and found to be precise and accurate.